High temperature (800 °C) oxidation of AISI 441 stainless steel with Mn–Co contact layers for SOFC stacks. (1st February 2022) - Shong, Wei-Ja; Liu, Chien-Kuo; Kao, Wei-Xin; Cheng, Yung-Neng; Lee, Ruey-Yi
Abstract: Characteristics of stainless steel grade AISI 441 deposited with Mn, Co and 10 wt% La0·6 Sr0·4 CoO3-δ (LSC) powder mixtures as cathode contact materials in solid oxide fuel cell (SOFC) stacks are studied. Microstructures of both uncoated and coated steel are examined after ageing at 800 °C for 10, 000 h in air. It is found that the free surfaces of both uncoated and Mn–Co coated (Mn/Co ratio = 1:2 and 2:1) steel coupons suffer severe oxide scale spallation. In contrast, on the contact surfaces of uncoated coupons Mn–Cr–Fe spinels develop; and Mn–Co spinels grow on Mn–Co and Mn–Co-LSC coated (Mn/Co ratio = 1:1) coupons. Precipitates of Ti, Si and Nb oxides segregate at the steel/scale interface, weakening scale adherence. Area specific resistance (ASR) of steel/powder/La0·6 Sr0·4 Co0·2 Fe0·8 O3-δ (LSCF) assemblies is measured at 800 °C for 5043 h in air. The Mn–Co-LSC mixtures (Mn/Co ratio = 1:1 and 1:2) display close ASR values of 21–24 mΩ cm 2, less than the value of 71 mΩ cm 2 from the Mn–Co mixture (Mn/Co ratio = 2:1). This is attributed to the lower intrinsic resistivity of the derived Mn–Co oxides as well as good contact with steel and the LSCF wafer. Highlights: AISI 441 suffers scale spallation on the free surface during cooling from 800 °C. Ti, Si and Nb precipitates segregate along steel/scale interface and weaken scale adherence. Oxides derived from Mn1–Co1 and Mn1–Co2 powders possess lower resistivity than that from Mn2–Co1. Oxides derived from Mn1–Co1 and Mn1–Co2 powders show good contact with LSCF cathode.